A New Species of Dodecacius Schwarz (Coleoptera: Elateridae) from Madre de Dios, Peru - Johnson, Paul J. (2017)
Dodecacius Schwarz is reviewed, it includes two species known only from the eastern lower slopes of the Andes and adjacent Amazonia in southeastern Peru. Dodecacius paititi new species is described. Dodecacius testaceus Schwarz is treated as a new synonym of D. nigricollis Schwarz.